Protective effects of different antioxidants and amrinone on vancomycin-induced nephrotoxicity - Celik, I; Cihangiroglu, M; Ilhan, N; Akpolat, N; Akbulut, HH (Wiley, 2005)
We have studied the effects of three antioxidants and amrinone, an inotropic agent, against vancomycin-induced nephrotoxicity in rats by investigating renal function and morphology. Thirty adult female Sprague Dawley rats (168-234 g) were divided into six groups. A saline-treated group served as control. The other five groups were treated for 7 days with vancomycin alone or in combination with alpha-lipoic acid, Ginkgo biloba extract 761, melatonin or amrinone. On day 8, all the rats were sacrificed by decapitation, kidney tissues were excised immediately and blood and kidney samples were collected. Blood urea and creatinine, kidney tissue malondialdehyde levels, and kidney superoxide dismutase and glutathione (GSH) peroxidase activities were measured. The kidneys were also examined for histological changes. Vancomycin administration led to increased urea, creatinine and malondialdehyde levels and decreased superoxide dismutase and GSH peroxidase activities. Co-administration of alpha-lipoic acid, Ginkgo biloba extract, melatonin or amrinone with vancomycin prevented the increases in the urea, creatinine and melondialdehyde levels and also resulted in higher superoxide dismutase and GSH peroxidase activities. The antioxidants and AMR improved the renal pathology compared to rats treated with vancomycin alone (P < 0.05). These results indicate that the three antioxidants and amrinone have potential protective effects against vancomycin-induced nephrotoxicity, which might in part be due to inhibition of free oxygen radical production. Amrinone was the most effective drug as judged on the basis of the pathological findings.
Keywords: Gentamicin-Induced Nephrotoxicity; Acute-Renal-Failure; Alpha-Lipoic Acid; Oxidative Stress; Tobramycin Nephrotoxicity; Superoxide-Dismutase; Free-Radicals; Melatonin; Rats; Injury